Synthesis of High-Yield Gold Nanoplates: Fast Growth Assistant with Binary Surfactants. (23rd May 2010) - Wang, Changshun; Kan, Caixia; Zhu, Jiejun; Zeng, Xiaoling; Wang, Xiangfu; Li, Hongchen; Shi, Daning
Abstract : A novel and simple chemical method was developed to fastly synthesize Au nanoplates with size of micrometers and tens of nanometers in thickness. The synthesis was carried out within 30 minutes by thermal reduction of precursors (HAuCl4 ) in the presence of binary surfactants Poly(vinylpyrrolidone) (PVP) and cetyltrimethylammonium bromide (CTAB) in ethylene glycol (EG) solution. The presence and concentration of PVP and CTAB in the growth solution play important roles in the fast formation of Au nanoplates. The obtained Au nanoplates exhibit strong surface plasmon absorption in the near-infrared region (NIR), displaying a considerable dependence on the shape and size. Characterizations by Transmission electron microscope and X-ray diffraction indicated that the nanoplates are single crystals with (111) planes as two basal surfaces. Explanations for the nuclei formation and crystal growth behind anisotropic Au nanoplates were proposed.